Numerical analysis with experimental validation of single-phase fluid flow in a dimple pattern heat exchanger channel - Močnik, Urban (Strojniški vestnik, 2020)
A plate heat exchanger with a dimple pattern heat plate has a large number of dimples. The shape of dimples defines the characteristics of the plate heat exchanger. Although such heat exchangers have become increasingly popular due to their beneficial characteristics, knowledge of the flow characteristics in such kind of channel is poor. A good knowledge of the flow conditions inside of such channel is crucial for the successful and efficient development of new products. In this paper single-phase water flow in dimple pattern plate heat exchanger was investigated with application of computational fluid dynamics and laboratory experiments. Numerical analysis was performed with two turbulence models, Realizable k%% with enhanced wall treatment function and k%% SST. The first predicts a slightly smaller pressure drop and the second slightly larger compared to the results of laboratory measurements. Our research found that despite the relatively low velocity of the fluid, turbulent flow occurs in the channel due to its shape. We also found that there are two different flow regimes in the micro plate heat exchanger channel. The first regime is the regime that dominates the heat transfer, and the second is the regime where a recirculation zone appears behind the brazing point, which reduces the surface for heat transfer. The size of the second regime does not change significantly with the velocity of the fluid in the volume considered.
Keywords: CFD; computational fluid dynamics; dimple pattern; heat exchanger; jamičasta struktura; model turbulence; prenosnik toplote; pressure drop; tlačni padec; turbulence models